The identification of cultural symbols in Maybank advertisements by malay university students - Fikriyudin,; Ramdani, M. R.; Abdullah,; Mokhtar, Aida (Universiti Putra Malaysia, 2020)
Premised on identification theory, the purpose of the study was to examine Malay university students’ identification of cultural symbols in advertisements by Malayan Banking Berhad (Maybank). Malaysia has a multicultural populace encompassing three main ethnic groups: the Malays, Chinese and Indians. Major festivals such as Eid al-Fitri, Chinese New Year and Deepavali are celebrated through festive advertisements by brands in Malaysia. For advertisements to be localised and resonate with the diverse Malaysian audience they ought to encompass cultural symbols that the audiences across different ethnicities are familiar with. Identification theory espouses the idea that connections can be made between the advertiser and target audience when there are shared understandings found in advertisements. Culture encompasses tangible and intangible components that represent cultural symbols. Interviews were conducted with university students who were also Maybank customers. The themes generated from the identification of cultural symbols in Maybank’s recent festive advertisements were customary practices for festivals, traditional attire of Malaysia, different languages used in Malaysia, and family relationships. When asked on how the students identified with the advertisements, the themes: the value of family relationships and the strong Maybank brand identity were generated. Most students recalled a recent Chinese New Year Maybank advertisement and identified with the Chinese cultural symbols. The study proved that the amount of shared understanding between the Malays and Chinese found through the identification of cultural symbols in Chinese New Year advertisements by the Malays was high and that identification theory works across ethnicities in Malaysia with the festive advertisements serving as platforms of shared understanding. Festive advertisements although celebrating festivals of different ethnic groups should be produced to unite the diverse populace in Malaysia for improved ethnic integration and nation building through more common symbols.